YELLOWSTONE I OŽIVLJAVANJE VESTERNA - Polić, Vanja (Anafora, 2024)
The article analyzes certain tenets of the Western genre in the series Yellowstone (2018-2023), drawing on the Western genre theory (Tompkins, Cawelti, Mitchell). It examineshow much the genre’s defining features – landscape, cowboy, horse, death, movement across space, and wilderness/civilization – function today in a traditional Western like Yellowstone, and why they still appeal to mainstream audiences. A discussion of the processes of transformation of lived experience of white settlers in the American West into the myth of the origin of the American nation (Slotkin), is then connected to the genesis of the Western, from a pseudo-realistic genre into a mythical one. In other words, the article explores the mythopoetic charge of the Western, which in large part creates the myth of the American nation that, like the Western, is traditionally narrated from the white settler perspective. Furthermore, the article analyzes the Western’s insistence on authenticity of life in the American (white) West. Using the argument of genre authenticity, the article shows how Yellowstone, relying on the ‘spectacularity’ of the old Wild West shows (e.g. Buffalo Bill’s Wild West), remains firmly entrenched within the traditional Western genre. Yellowstone rhetorically and visually insists on its depiction of the ‘authentic’ way of life in today’s American West, incorporating many elements of the mythopoeia of American society. Also, as a true soap opera (horse opera), it unintentionally exposes those old values as hypocritical, one-sided, and self-serving, indicating the shortcomings of that praised ‘American’ way of life.